2002
DOI: 10.1046/j.1365-2842.2002.00876.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and physical properties of resin modified glass‐ionomers combined with chlorhexidine

Abstract: The purpose of this study was to determine the effect on mechanical properties and antimicrobial activity of the addition of chlorhexidine (CHX) to a resin modified glass-ionomer (Photac-fil, ESPE, Norristown, PA, USA). Chlorhexidine diacetate was combined with a resin modified glass-ionomer material at a concentration of 5%. The samples were tested for hardness, tensile strength and erosion at 24 h and 6-week intervals and for elution of CHX and antimicrobial activity weekly for 6 weeks. At 24 h there was no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
117
3
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(129 citation statements)
references
References 9 publications
7
117
3
2
Order By: Relevance
“…The largest number of studies analyse the antimicrobial effect of the chlorhexidine compound in the form of diacetate, gluconate, digluconat, hydrochloride or dihydrochloride, incorporated in conventional and modifi ed glass-ionomer cements, most often in the powder of the glass-ionomer cements (14,16,17,18,29,31). The antimicrobial effect against the cariogenic microorganisms Streptococcus mutans, Lactobacillus casei and Actinomyces viscosus is most often analysed (16,18,29,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest number of studies analyse the antimicrobial effect of the chlorhexidine compound in the form of diacetate, gluconate, digluconat, hydrochloride or dihydrochloride, incorporated in conventional and modifi ed glass-ionomer cements, most often in the powder of the glass-ionomer cements (14,16,17,18,29,31). The antimicrobial effect against the cariogenic microorganisms Streptococcus mutans, Lactobacillus casei and Actinomyces viscosus is most often analysed (16,18,29,31).…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve the antimicrobial characteristics of both conventional and resin-modifi ed glass ionomer cements (RMGIC), antimicrobial compounds have been added. In a number of studies the most frequently analyzed antimicrobial agent is chlorhexidine (14)(15)(16)(17)(18), although there are few data about incorporation of other antimicrobials. Cetylpirydinium Chloride (C 21 H 38 NCl) (CPC), as an active component of oral antiseptics has a broad antimicrobial spectrum, with strong bactericidal effect on Gram-positive pathogens and a fungicidal effect on fungi.…”
Section: Introductionmentioning
confidence: 99%
“…This association is aimed at reducing severity and frequency of secondary caries by decreasing failures and unsuccessful use of these restorative materials 6,7,12,25 . Based on the observation of the presence of viable bacteria in the remaining dentin after removal of the infected layer and proper sealing of the cavity researchers observed that under in vitro conditions the addition of CHX to the GIC showed favorable antibacterial effect against microorganisms such as Streptococcus mutans, Lactobacillus spp., Candida albicans and Actinomyces naeslundii, acts on the biofilm act on the biofilm, which begins to show less pathogenic composition compared to acidogenic biofilm with a predominance of S. mutans, which would be formed without the presence of the antibacterial agent 3,9,[11][12][13][14]23,25 Türkün et al 3 demonstrated that GIC and CHX at a concentration of 0.5% have a long-term antibacterial effect without compromising the physical properties of the restorative material. However, concentrations at 1.25 and 2% weaken the material by compromising its physical properties, such as resistance to erosion, compression, diametrical traction, flexion, setting time, and surface hardness 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been carried out in order to incorporate antibacterial agents to GICs 3,5,6,7,[11][12][13][14] , such as CHX at different concentrations, showing effective results for certain microorganisms under in vitro conditions (Streptococcus mutans) 3,6,12 . Nevertheless, the incorporation of antibacterial agents into restorative materials can result in changes in their physical properties depending the concentration used 3,5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…When the tissue conditioners were immersed in heart infusion agar medium, the bamboo extracts scarcely eluted, and the adhesion of Candida albicans to tissue conditioners containing 10 wt% bamboo extracts was significantly inhibited. The antimicrobial activity of resin modified glass-ionomer material combined with chlorhexidine at a concentration of 5% was studied 7) . The material exhibited a significant reduction in Streptococcus mutans numbers for 1−3 weeks, but after four weeks there was no difference between glass-ionomers with and without chlorhexidine.…”
Section: Introductionmentioning
confidence: 99%